A Comparative Study on the Effectiveness of Iron (Fe) Adsorption from Acid Mine Drainage Using Single and Composite Adsorbents - Mycelia Paradise; Yudha Agung Pratama; Faisol Mukarrom; Triyono Triyono; Akhmad Zamroni (Unversitas Muhammadiyah Mataram, 2026)
Acid mine drainage (AMD) is mining waste that has high acidity and dissolved metal content, especially iron (Fe), which has the potential to pollute the aquatic environment. This research aimed to evaluate the performance of coconut shell activated charcoal and local composite-based adsorbents (active charcoal–clay–zeolite) in reducing Fe concentrations in AMD. The research was conducted using two types of samples: real AMD collected from the mine site and synthetic AMD prepared in the laboratory using a FeSO₄·7H₂O solution. The composite adsorbent was tested using real AMD (baseline pH 2.6; Fe 42.75 ppm), while activated charcoal was tested on synthetic AMD (baseline pH 4.7; Fe 40.37 ppm). The main variables observed were dissolved Fe concentration and pH changes at various contact time variations. Analysis of Fe concentrations was carried out using AAS, while pH was measured directly with a pH meter. Adsorbent characterization was performed with BET to identify the specific surface area of the adsorbents. Results showed that activated charcoal was able to increase pH to 8.6 and decrease Fe to 0.04 ppm (99.9% efficiency). The primary mechanism of Fe reduction is dominated by Fe(OH)₃ precipitation, which occurs due to an increased pH. In contrast, the composite produced a final pH of 4.3 but still decreased Fe to 0.52 ppm (98.8% efficiency). BET analysis showed that although activated charcoal had a greater surface area, the composite maintained better pore stability after adsorption. The integration of the two has the potential to enhance the adsorption effectiveness and stability in the field for the remediation of acid mine drainage.